Household food insecurity in South Africa from 1999 to 2021: a metrics perspective - Louise van den Berg; Corinna May Walsh (Cambridge University Press, 2023)
Abstract Objective: To review and synthesize studies on household food security in South Africa. Design: Systematic mapping review of metrics (methodological review). Setting: Electronic databases, including EBSCOHost, Scopus and Web of Science, were searched for studies and reports on household food security in South Africa, reporting household food security published between 1999 and 2021. Searching, selecting and reporting were performed according to the PRISMA (Preferred Reporting Items for Systematic reviews and Meta-Analyses) statement. Participants: South African households Results: Forty-eight articles reporting on six national surveys (one repeated annually since 2002) and forty sub-national studies meeting the inclusion criteria were selected. Various metrics, with different recall periods and ways of categorizing food security levels, were identified. Surveys that used similar metrics showed that the percentage of South African households that have experienced food insecurity and hunger has decreased over the review period yet remains concerning. However, the multitude of metrics used to assess the different components and levels of food security limits the comparability of the results to evaluate the scope and scale of the problem. Conclusions: There is growing support for developing multi-variable approaches for food security research in sub-Saharan Africa. Future research should focus on finding the most appropriate combination of complementary metrics that would allow comparable data while holistically capturing food security and providing insight into the causes and consequences.